Literarno-kulturni kodi v pesniškem jeziku najnovejše poljske lirike - Dąbrowska, Elżbieta (Slavistična revija, 2002)
The article discusses recent Polish poetry (of the 1990's) from the perspective of its connection with the codes formed witin the literary tradition (references to styles, forms and genres). The author presents the strategies in which the old styles are present in contemporary poetry and attempts to explain the peculiar character of the poetry of 'classicists' (neo-classicists), who - in contrast to the 'barbarians' - in turning to tradition found ready-made language to be used for the discussion of contemporary themes. Alleged continuation, polemic dialogues, parody- and irony-like modes of discourse became a 'semantic gesture' of the contemporary poet, including, among others, Krzysztof Koehler, Edward Tkaczyszyn-Dycki, Tomasz Majeran, and Wojciech Wencel.
Keywords: literarna tradicija; Polish literature; poljska književnost; poljska poezija; tekstna lingvistika